Perception and Willingness-to-Pay on conservation of lake basin under the impact of climate change – a comparison between urban and rural tropical lake - Zati Sharip,; Abd Ghani Awang Noor, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Climatic changes are affecting the lake hydrological regime, including the associated drought and floods within the drainage basins. Assessing the value of damages to ecosystem services within the lake basin concerning the climatic changes is difficult due to the numerous ecosystem services provided by every lake basin. This study uses a Contingent Valuation Method to determine the willingness-to-pay (WTP) for lake conservation programs for addressing climate extreme impacts on urban and rural tropical lakes. Surveys using structured questionnaires were carried out around Putrajaya, the Federal Territory of Putrajaya (urban lake) and around Muda Lake, Kedah (rural lake). Respondents in both lake basins significantly differed in terms of education and income level. However, the WTP values for contribution to address climate change measures in both lakes were similar (around USD3). About 62% of respondents in both lake basins were willing to pay and contribute to climate change and conservation trust funds for preventing impacts on the lake. For Putrajaya Lake, the main reason for WTP was the need for managing lake and wetland, and their biodiversity while for Muda Lake, the main reason for WTP was the need for circumventing deterioration in the lake for future generations.